Ileocaecal ménage a trois: a rare case presentation - Mungazi, Simbarashe Gift; Zambuko, Blessing; Ngulube, Allan; Gwini, Rudo; Muchuweti, David (Elsevier, 2021)
We report a case of a 32-year-old Black African male, newly diagnosed with Human Immunodeficiency Virus (HIV) infection, who presented with symptoms and signs of an acute abdomen. The patient presented with a three-week history of diarrhoea and a five-day history of severe generalised abdominal pain with fever. The patient took alcohol and was a smoker (15 pack years). The past medical was non-contributory. On physical examination the patient was ill-looking and in severe pain. The core body temperature was 37.5 °C. Abdominal examination revealed generalised tenderness and right iliac fossa guarding and tenderness associated with a palpable mass. The Complete Blood count (CBC) and serum Urea and Electrolyte levels were within normal limits. The CD4 count was 563 cells/μl. An ileocaecal mass was identified on exploratory laparotomy and histopathological examination of the right hemicolectomy resection specimen showed extensive involvement of the terminal ileum and caecum by caseating epithelioid granulomata accompanied by Langhans-type multinucleated giant cells typical of Tuberculosis. The Ziehl-Neelsen stain was positive for alcohol and acid fast bacilli (AAFBs). An additional lesion represented by nodules of a synaptophysin- positive carcinoid tumour (Neuroendocrine tumour grade 1, NET G1) was identified in the distal appendix and caecal submucosa, with each nodule measuring less than 1 cm across. The incidental presence of innumerable calcified and non-calcified (viable) Schistosoma ova completed the rather unusual constellation of pathological findings in this patient (Figs. 1 and 2).